Deleuze and Collaborative Writing in the Dance of Activism. Issue 3 (August 2019) - Gale, Ken; Wyatt, Jonathan; Gullion, Jessica Smartt; Hou, Ninian; Jeansonne, Christopher; Linnell, Sheridan; Reaves, Melanie A.; Reilly, Rosemary; Rhodes, Paul
Drawing upon and infused by the 'micropolitical' moves of Deleuze and Guattari, this article arose out of a participative workshop at the 2018 International Congress of Qualitative Inquiry that took up Braidotti's proposition to explore how collaborative writing 'like breathing, [is] not held into the mould of linearity, or the confines of the printed page, but move[s] outwards, out of bounds, in webs of encounters with ideas, others, texts' (Braidotti, 2013, p. 166). We worked with the view that collaborative writing is a political act, a 'minor gesture' (Manning, 2016), a world making that opens up to the new and challenges the sedimented. This is an article that engages in and with collaborative writing, that dances with ideas of what collaborative writing might be and, crucially, what it might do .